Pemanfaatan Podcast Sebagai Sarana Transformasi Mindset Mahasiswa: Studi Podcast “Bahas Aja Eps Gen Z, Malas & Pengangguran” - Ita Hidayati; Hafna Nadhifa Syarifa; Muhammad Kevin Kadhafi; Moch. Aldi Azizul Hakim; Kamunoyoso Agung Nugroho; Rifqi Rohmanul Khakim (Yayasan Al-Afif, 2026)
Negative Stereotypes Regarding Gen Z's Work Ethic, Such As Laziness And Lack Of Discipline, Continue To Develop In Society And Potentially Influence The Identity Formation Of Young Generations. This Study Aims To Examine The Effectiveness Of Podcasts As A Medium For Transforming Students' Mindset, Taking A Case Study Of The Episode